Multiple trends of tertiarization: A comparative input-output analysis of the service sector expansion between Brazil and United States - Kênia Barreiro de Souza; Suzana Quinet de Andrade Bastos; Fernando Salgueiro Perobelli (EconomiA, 2016)
The service sector expansion has shown to be a multiple trend process, producing distinct sectorial compositions. The present paper aims to make a comparison between two large economies in different stages of development with an extensive service sector (Brazil and United States), by focusing on final and intermediary demand changes and sectorial productivity as well. Input–output matrices for Brazil and United States were used and two applications were carried out: structural decomposition analysis and total factor productivity. Main results are as follows. Firstly, the growth in services was fostered by several factors, among which household consumption assumes an important role for both countries. Second, inter-industrial linkages play a major role only for United States. Thirdly, there is now evidence of cost disease for Brazil. Finally, productivity is lower in Brazil, nonetheless labor productivity increased above the average in some service sectors. – – A expans\~ao do setor de serviços tem se mostrado um processo de múltiplas tendências, produzindo composiç\~oes setoriais distintas. O presente artigo tem por objetivo fazer uma comparaç\~ao entre duas grandes econômicas em diferentes estágios de desenvolvimento e com um extensivo setor de serviços (Brasil e Estados Unidos), focando em mudanças na demanda intermediária, final e também na produtividade setorial. Matrizes insumo-produto do Brasil e Estados Unidos foram utilizadas e duas aplicaç\~oes foram realizadas: análise de decomposiç\~ao estrutural e produtividade total dos fatores. Os principais resultados s\~ao os seguintes. Primeiramente, o crescimento do setor de serviços foi fomentado por diversos fatores, entre os quais o consumo das famílias assume papel importante para ambos os países. Em segundo lugar, as ligaç\~oes inter-setoriais exercem um papel de destaque apenas para os Estados Unidos. Terceiro, n\~ao existe evidência da doença dos custos para o caso do Brasil. Finalmente, a produtividade é mais baixa no Brasil, embora a produtividade dos serviços tenha crescido acima da média para alguns setores de serviços.
Keywords: C67; L8; R15; 330; Tertiarization; Input-output; Development